Isolation, Encapsulation, Stability and Characteristics of Thylakoid from Suji Leaves (Pleomele angustifolia) as Natural Food Coloring Agent - Chandra, Rosita Dwi; Indrawati, Renny; Heriyanto, Heriyanto; Brotosudarmo, Tatas H.P.; Limantara, Leenawaty (Indonesian Journal of Natural Pigments, 2019)
Suji (Pleomele angustifolia) is one kind of Indonesian typical plants which can be used as natural green food coloring agent. The susceptibility of natural pigment to external environment forces the protection in order to prolong its shelf life. Encapsulation has been known in the art of food preparation to provide protection for several ingredients including food coloring agent. The objective of this study was to observe the method for isolation and encapsulation of thylakoid, and to investigate the stability and characteristics of thylakoid of suji leaves encapsulated in maltodextrin during dark storage at 30 °C, 45 °C, and 60 °C. The degradation of the encapsulated pigments was identified through chromametric analysis which resulted in the increase of L* (lightness), a* (redness), and b* (yellowness) values. In addition, it was also indicated by the decrease of total chlorophyll (TC) which was determined using spectrophotometer. Chromatography analysis confirmed the presence of four major peaks in the fresh encapsulated thylakoid powder and five major peaks in the encapsulated thylakoid powder stored at the highest temperature (60 °C), with Chl a as the dominant pigments in both powder. The vivid green powder was able to preserve its color without any obvious change to an untrained eye up to 60 d of storage at 30 °C, becoming a promising ingredient to replace the synthetic colorants.